Sosialisasi Pembangkit Listrik Tenaga Bayu (PLTB) sebagai Solusi Energi Berkelanjutan di PT. PLN Nusantara Power - Moh. Syaiful Anwar; Bambang Triono; Mochamad Shaleh (LP3M INSTITUT KH YAZID KARIMULLAH, 2025)
This community service activity aims to improve renewable energy literacy, particularly Wind Power Plants (Pembangkit Listrik Tenaga Bayu/PLTB), among employees of PT. PLN Nusantara Power. The program was conducted on May 17–18, 2025, involving 15 participants from the electricity generation operational environment. The implementation method consisted of preparation, two socialization sessions, a focus group discussion (FGD), and evaluation through pre-test and post-test assessments. The materials covered basic wind energy concepts, PLTB working principles, system components, development potential in Indonesia, and implementation aspects within power systems. The results indicated an increase in participants’ understanding, reflected in higher post-test scores compared to pre-test results. In addition, the FGD results showed that participants were able to identify opportunities, challenges, and implementation strategies for PLTB in their work environment. This activity demonstrates that an educational and participatory approach is effective in improving understanding and enhancing analytical thinking regarding renewable energy topics.